Polarimetric Radar Data from the Ross and Amundsen Sea Ice Flow Divide, West Antarctica - Matsuoka, Kenichi; Power, Donovan; Fujita, Shuji; Raymond, Charles (NSIDC: National Snow and Ice Data Center, 2014)
This dataset contains ground-based, co-polarized radar data collected using pulse-modulated 60 MHz and 179 MHz radar at 19 sites around a deep ice coring site near the Ross and Amundsen flow divide of West Antarctic Ice Sheet (WAIS Divide). At each site, the radar data were collected at 12 orientations of the radar polarization plane for three radar pulse widths: 250 nsec, 500 nsec, and 1000 nsec. Useful signals were received from depths roughly between 200 m and 2000 m. Ice flow velocities and strain configurations were measured at most of these radar survey sites, and these ice motion data are also provided at NSIDC (GPS-Measured Ice Velocities and Strain Data from the Ross and Amundsen Sea Ice Flow Divide, West Antarctica).